Guide for evaluation of the sustainability of formworks - Benavides, Stefany (2024)
El continuous growth of the construction industry is directly linked to significant environmental impacts. According to the United Nations Environment Programme (UNEP) in 2020, the operation and construction of buildings contribute to 38% of all carbon dioxide (CO2) emissions related to energy. UNEP emphasize the need for a three-fold strategy to address this issue: aggressively reduce energy demand in built areas, decarbonize the energy sector, and implement material strategies that reduce carbon emissions throughout the lifecycle of products. To quantify the Carbon Footprint, an approach called Life Cycle Assessment (LCA) is used, which involves assessing the impact on climate change by considering the entire value chain of a product or service, including inputs and greenhouse gas (GHG) emissions. To evaluate the sustainability of a formwork, it is necessary to evaluate the carbon footprint of the formwork at different stages: I. Understanding the stages and processes of the life cycle of a construction material. II. Identifying the stages and processes of the life cycle of a formwork in which GHG emissions are generated. III. Selecting the stages and their respective processes to evaluate in the life cycle of a formwork. IV. Recognizing the resources and raw materials consumed capable of emitting GHGs. V. Quantifying the amount of resources and raw materials required for the production of a formwork unit. VI. Finding the equivalent CO2 emission factor for the required resources and raw materials. VII. Estimating the carbon footprint for the manufacturing of a formwork unit. It can be concluded that in order to estimate the carbon footprint of manufacturing a formwork unit, it is necessary to use the following formula: Carbon footprint = Activity Data × Emission Factor. Additionally, it is necessary to calculate the carbon footprint produced by the consumption of electricity and water during the manufacturing process of the metal formwork by multiplying the quantities consumed per formwork unit by their respective emission factors and adding both values.